Direct and Inverse Optimization Problems in a Gas Deposit Model - Skiba, Alexander (2022 15th International Conference Management of large-scale system development (MLSD), 2022)
A continuous dynamic model for the development of a gas field is studied. Two mathematical problems are posed, solved and analyzed. In the direct problem, we are looking for the maximum accumulated profit on a set of temporary functions of a certain type. In the inverse optimization problem, we define the entire set of planning horizons. We subject the assigned tasks to a comprehensive analysis.